2022
DOI: 10.3390/app12031595
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning Based Detection of Missing Tooth Regions for Dental Implant Planning in Panoramic Radiographic Images

Abstract: Dental implantation is a surgical procedure in oral and maxillofacial surgery. Detecting missing tooth regions is essential for planning dental implant placement. This study proposes an automated method that detects regions of missing teeth in panoramic radiographic images. Tooth instance segmentation is required to accurately detect a missing tooth region in panoramic radiographic images containing obstacles, such as dental appliances or restoration. Therefore, we constructed a dataset that contains 455 panor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…This shows the excellent performance of tooth cutting and tooth positioning presented in this article. Compared with the 92.78% and 92.14% accuracy rates in [14] and [15], the accuracy rate in this study showed a 0.5% improvement as listed in Table Ⅳ. Even compared with 79.00% of the literature [13], the proposed method is a huge improvement.…”
Section: A the Performance Of The Tooth Cutting Algorithmmentioning
confidence: 55%
See 3 more Smart Citations
“…This shows the excellent performance of tooth cutting and tooth positioning presented in this article. Compared with the 92.78% and 92.14% accuracy rates in [14] and [15], the accuracy rate in this study showed a 0.5% improvement as listed in Table Ⅳ. Even compared with 79.00% of the literature [13], the proposed method is a huge improvement.…”
Section: A the Performance Of The Tooth Cutting Algorithmmentioning
confidence: 55%
“…AlexNet has 95.2% which is relatively low. The overall accuracy of the method in this paper is above 95% , which is greatly improved compared with the methods in the current state-of-the-art [15] and [33]- [34].…”
Section: B Comparison Of Different Cnn Networkmentioning
confidence: 77%
See 2 more Smart Citations
“…The primary version is composed of 1500 pairs of panoramic radiographs and binary masks of the pixel regions of the teeth in each radiograph, for semantic segmentation. One article combined the UFBA-UESC dataset with their own dataset [41].…”
Section: Datasetsmentioning
confidence: 99%